2015
DOI: 10.1038/npp.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Antidepressant Action and Restoration of Excitatory Synaptic Strength After Chronic Stress by Negative Modulators of Alpha5-Containing GABAA Receptors

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are the primary pharmacological treatment for depression, but SSRIs are effective in only half of the patients and typically take several weeks to relieve symptoms. The NMDA receptor antagonist ketamine exerts a rapid antidepressant action, but has troubling side effects. We hypothesized that negative allosteric modulators of GABA A receptors would exert similar effects on brain activity as ketamine, but would not exert as many side effects if targeted only to GA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 66 publications
5
70
0
Order By: Relevance
“…In rats, ketamine administration at sub-anesthetic doses results in a significant increase in extracellular glutamate levels 35 and an increase in glutamate cycling 44 in the prefrontal cortex. Further supporting this hypothesis, administration of partial inverse agonists at the benzodiazepine binding site of alpha5-containing GABA A receptors, which are selectively expressed in the forebrain, including prefrontal cortex and hippocampus, promote coherent network activity via disinhibition of excitatory neurotransmission 45 and exert rapid antidepressant actions in several animal tests 4648 . Notably, ketamine 13 , similar to negative allosteric modulators of alpha5-containing GABA A receptors 47 , enhance gamma band electroencephalography power, which is hypothesized to be directly related to cortical disinhibition 4952 , further supporting the role of cortical disinhibition in the rapid antidepressant actions of these drugs.…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 85%
“…In rats, ketamine administration at sub-anesthetic doses results in a significant increase in extracellular glutamate levels 35 and an increase in glutamate cycling 44 in the prefrontal cortex. Further supporting this hypothesis, administration of partial inverse agonists at the benzodiazepine binding site of alpha5-containing GABA A receptors, which are selectively expressed in the forebrain, including prefrontal cortex and hippocampus, promote coherent network activity via disinhibition of excitatory neurotransmission 45 and exert rapid antidepressant actions in several animal tests 4648 . Notably, ketamine 13 , similar to negative allosteric modulators of alpha5-containing GABA A receptors 47 , enhance gamma band electroencephalography power, which is hypothesized to be directly related to cortical disinhibition 4952 , further supporting the role of cortical disinhibition in the rapid antidepressant actions of these drugs.…”
Section: Nmdar Inhibition-mediated Mechanismsmentioning
confidence: 85%
“…This can be achieved by enhancing GABAergic signaling through α5-GABA A Rs. Indeed, selectively modulating α5-GABA A Rs with α5-selective PAM and NAM compounds induces antidepressant-like effects in rodents [18, 28]. Although the reason for converging effects from opposite modulatory mechanisms is not yet understood, it has been suggested that SST cell regulation of cortical microcircuit activity by α5-GABA A R potentiation follows an inverted U curve to promote therapeutic efficacy, or alternatively that short-term inhibition leads to recurrent potentiation through cortical feedback loops, similar to recent findings on the mechanisms of rapid-acting antidepressants [19].…”
Section: Discussionmentioning
confidence: 99%
“…1), presumably through a disinhibition of excitatory glutamatergic neurotransmission [161]. Specifically, administration of GABA-NAMs that are selective for receptors containing alpha5 subunits, such as L-655,781 or MRK-016, reversed social interaction and sucrose preference deficits following several chronic stress paradigms 24 h after administration in rats [162]. The effects of a single injection were long-lasting since decreases in behavioral despair in the forced-swim test and restoration of sucrose preference deficits could be seen up to 7 days post-treatment [163].…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…Chronic stress-induced decreases in hippocampal GluA1 expression are also rapidly reversed following a single dose of a selective GluN2B antagonist [90] or an alpha5-selective GABA-NAM [162]. An increase in AMPAR expression in specific synapses is likely to be indicative of a potentiation of AMPAR-mediated synaptic transmission following administration of rapid-acting antidepressants.…”
Section: Downstream Pathways Involved In Rapid Antidepressant Actionsmentioning
confidence: 99%